2008
DOI: 10.1089/lap.2007.0226
|View full text |Cite
|
Sign up to set email alerts
|

Management of Abdominal Compartment Syndrome in a Very Low Birth Weight Neonate Using Penrose Drains and Subsequent Management of Abdominal-Wall Defects

Abstract: Percutaneous drainage of the peritoneal cavity has been recently evaluated for the treatment of perforated viscous in the very low birth weight (VLBW) neonate and percutaneous decompression for abdominal compartment syndrome (ACS) has been studied in older patient populations. This is the first reported case of using this technique to treat ACS in a VLBW neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Needle decompression was reported in a child with ACS resulting from tension pneumoperitoneum [45]. The successful use of a Penrose drain has been reported in a very-low-birth-weight (VLBW) neonate weighing only 650 gm [75]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Needle decompression was reported in a child with ACS resulting from tension pneumoperitoneum [45]. The successful use of a Penrose drain has been reported in a very-low-birth-weight (VLBW) neonate weighing only 650 gm [75]. …”
Section: Resultsmentioning
confidence: 99%
“…Latenser et al's study reported peritoneal contamination that did not progress to peritonitis in one patient [14]. The VLBW neonate developed hernias at the catheter insertion sites upon removal of the Penrose drain, resulting in the need for reconstructive laparoscopic surgery [75]. Some patients have progressed to death in spite of decompression by catheter placement [49].…”
Section: Resultsmentioning
confidence: 99%
“…Known to lead to multi-organ dysfunction in adults and children [11][12][13], ACS is also associated with high pediatric mortality (40-60%) [8,13,14]. Although IAH and ACS are not frequently reported in the neonatal literature, there are case reports indicating that ACS can complicate neonatal extra corporeal membrane oxygenation [15], and that abdominal decompression to treat ACS might be managed percutaneously in the small premature infant [16]. Some authors suggest that IAH and ACS occur at lower IAP in children.…”
Section: Discussionmentioning
confidence: 99%